Salivary Protein Biomarkers for Diagnosis of Oral Squamous Cell Carcinoma - Navale, Archana M.; Deshpande, Atharva; Mistry, Bini; Chauhan, Premal; Bhagat, Charansharan (Current Cancer Drug Targets, 2024)
OSCC (Oral Squamous Cell Carcinoma) is a major health challenge in many parts of the world. It occurs most commonly in males and is associated with tobacco, pan, or areca nut consumption. One of the major challenges associated with the management of OSCC is late diagnosis. As a result, the treatment required is more aggressive, expensive, and has poor prognostic value. On the other hand, early diagnosis of OSCC can be life-saving with less aggressive treatment and a better prognosis. A diagnostic method for early diagnosis of OSCC is greatly needed. A lot of research efforts have been made to identify biomarkers that can act as tools to classify the tumor status of the patient. Various biological fluids and tissues have been explored for such studies. Saliva appears to be the most attractive biological sample with many potential advantages over other matrices such as blood or tissue. Saliva as a diagnostic fluid has the advantage of ample availability, being non-invasive and being in the vicinity of the tumor, and having a less complex composition. Our paper provides an updated review of the state of the art of research in the area of salivary biomarkers for oral squamous cell carcinoma. The paper gives an account of methods for saliva collection, followed by a brief description of various protein biomarkers discovered to date, along with their status quo.
Keywords: liquid biopsy